The devil you know - Rocha, Kit (Rocha, Kit. Mercenary librarians novel., 2021)
"Maya, genetically engineered for genius and trained for revolution, vows to stop an operation trading in genetically enhanced children with the help of Gray, who, unable to escape the time bomb in his head, has found his purpose in his final days--keeping Maya safe"--